Application of Genetic Algorithm for Optimizing Continuous and Discrete PID to Control Antenna Azimuth Position - Nguyen, Binh-Hau; Cao, Hoang-Thanh-Tuan; Nguyen, Thai-Toan; Pham, Minh-Duc; Pham, Van-Thuan-Em; Nguyen, Tuan-Anh; Ho, Van-Nguyen; Ngo, Gia-Dat; Tran, Dinh-Nam-Phat; Le, Thanh-Dat; Phan, Cong-Duc-Quyen; Le, Van-Khai; Le, ThiHongLam (Journal of Fuzzy Systems and Control, 2024)
In the paper, we introduce a continuous and discrete PID optimization method by using genetic algorithm (GA) to analyze and control antenna position – a typical model in control engineering. From analizing kinematic equations of this model, we propose continuous and discrete PID controllers to stabilize it. The control result in the case of the empirically selected K matrix (Kp, Ki, Kd) is compared to the case of the K matrix optimized by GA. From this, we can compare the system's output response with the above continuous and discrete PID controllers. The results show that continuously and discrete optimized PID controllers by GA are better than PIC controllers from empirical test through simulation.